Analysis Of The Efforts Of Madrasah Principles In Improving Teachers Social Competence Through Clinical Supervision In MAS Muallimin Muhammadiyah Sawah Dangka - Hidayatullah, Nurfitri; Oktaviani, Oktaviani; Amarta, Yoga; Rifma, Rifma; Marsidin, Sufyarma (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
This study aims to analyze the efforts made by the head of the madrasa to improve the social competence of teachers through the application of clinical supervision at Mas Muallimin Muhammadiyah Sawah Dangka. A teacher's social competence has an important role in creating a conducive and effective learning environment for students. Therefore, the role of the madrasa head in improving the social competence of teachers is a critical factor in improving the quality of education. The research method used is the descriptive qualitative method. Data was collected through observation, in-depth interviews with madrasa heads and teachers, as well as documentation studies related to clinical supervision policies and programs that had been carried out. The results showed that the head of the madrasa at MAS Muallimin Muhammadiyah Sawah Dangka had implemented clinical supervision as a strategy to improve the social competence of teachers. Clinical supervision is carried out through several steps, such as studies documenting teacher condition data, class observations, joint reflection, group coaching, and follow-up. Through clinical supervision, principals provide constructive feedback to teachers and encourage them to develop their social competence. However, there are several challenges encountered in the implementation of clinical supervision, including teachers not being open about problems encountered, the lack of time available for clinical supervision, and the teacher's lack of consistency in implementing improvements as a follow-up to clinical supervision. Based on the findings, it is suggested that madrasa principals pay attention to and overcome the challenges faced in the implementation of clinical supervision. Madrasah heads also need to improve communication and collaboration with teachers to strengthen efforts to improve teacher social competence.   Keywords: Head Master, Teacher Social Competence, Clinical Supervision